Research of Signal Modulations of the Global Navigation Satellite System - Ергалиев, Д; Каримов, С; Советкажиев, А; Алимов, Д; Куандыкова, А; Социалов, Р (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
An universal approach is proposed to the study of signal modulations of the Global Navigation Satellite System. This approach allows us to explore both known and new types of signal modulation, as well as their combinations. Using the proposed approach, the information has been investigated efficiency of some modern known and new proposed varieties of signal modulation for implementing a satellite system. Multiple satellites must share the same transmission medium and broadcast to GNSS users to enable positioning. The first is binary phase shift keying. This type of modulation has found very wide application due to the high noise immunity and simplicity of the modulator and demodulator. Next in line is modulation with a biased offset carrier, which relates to a method and apparatus for receiving modulated radio navigation signals transmitted by the satellites of the navigation system, which make it possible to independently determine the position of the receiving equipment in its own coordinate system of this system.